Pengalaman ibu dalam merawat anak Dengan leukemia - Avanty - Maria; Ganis - Indriati; Siti Rahmalia HD (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
Leukemia is a blood disorder, as result of the proliferation of immature cell growth and malignant leukocytes. Leukemia are often accompanied by the presence of excessive amounts of leukocytes. Patients also had to do chemotherapy to prevent the spread of cancer cells. Important role in the treatment of leukemia can not be separated from the role of a mother. This qualitative research design used a descriptive phenomenological method, that aims to explored maternal experience in treating child with leukemia. The results of this research found four themes: 1) the first response, 2) attitude during treatment 3) support obtained, 4) the impact of the disease. The results of this study are expected to provide information to health care practitioners, especially nurses in pediatric room to given information that increased knowledge and to encourage children and their families Key words: leukemia, caring for children, mothers experience